2010
DOI: 10.1016/j.otsr.2009.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Infection risk prevention following total knee arthroplasty

Abstract: Level IV. Prospective prognostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 14 publications
0
9
2
1
Order By: Relevance
“…We next compared independent risk factors for infection in our patients to those in previously published studies that provided such detail (►Table 4). Compared with several different previously published studies, our population was more likely to be ASA > 2 (OR, 3.0-37.8; p < 0.001) [13][14][15]17,29,31,33,34 and to have a BMI > 30 (OR, 2.0-14.6; p 0.001). 15,17,29,33 We also demonstrate a higher incidence of immunosuppressed patients (OR, 5.7; p < 0.001) 33 and rheumatoid arthritis (OR, 1.2-4.4; p < 0.001-0.352).…”
Section: Population Comorbidity Analysiscontrasting
confidence: 56%
See 1 more Smart Citation
“…We next compared independent risk factors for infection in our patients to those in previously published studies that provided such detail (►Table 4). Compared with several different previously published studies, our population was more likely to be ASA > 2 (OR, 3.0-37.8; p < 0.001) [13][14][15]17,29,31,33,34 and to have a BMI > 30 (OR, 2.0-14.6; p 0.001). 15,17,29,33 We also demonstrate a higher incidence of immunosuppressed patients (OR, 5.7; p < 0.001) 33 and rheumatoid arthritis (OR, 1.2-4.4; p < 0.001-0.352).…”
Section: Population Comorbidity Analysiscontrasting
confidence: 56%
“…Large-scale database studies have demonstrated certain comorbidities to be significantly associated with an increased risk of SSI. [12][13][14][15][16][17][18] These include, but are not limited to, (1) American Society of Anesthesiologists (ASA) class > 2, (2) body mass index (BMI) > 30 kg/m 2 , (3) immune suppression, (4) rheumatoid arthritis, and (5) diabetes mellitus. [19][20][21][22][23][24] In our inner-city tertiary referral institution, which has been a focus of epidemic community-acquired MRSA (CA-MRSA) for over a decade, 25,26 it is perceived that many patients undergoing TKA have several comorbidities which substantially increase risk of SSI and that exposure to resistant organisms is high.…”
mentioning
confidence: 99%
“…Diabetes mellitus is also associated with SSI in patients undergoing arthroplasty [12,13], although the degree of attributable risk for infection independent of obesity is difficult to establish [6,30]. These risks may increase morbidity and mortality while also adding the burden of increased cost [15,18]. Additional patient risk factors include, but are not limited to, tobacco use, poor dentition, immunosuppression, methicillin-resistant Staphylococcus aureus (MRSA) colonization, malnutrition, inflammatory disease, and coagulopathy [5,6,18,21,23,25].…”
Section: Introductionmentioning
confidence: 99%
“…These risks may increase morbidity and mortality while also adding the burden of increased cost [15,18]. Additional patient risk factors include, but are not limited to, tobacco use, poor dentition, immunosuppression, methicillin-resistant Staphylococcus aureus (MRSA) colonization, malnutrition, inflammatory disease, and coagulopathy [5,6,18,21,23,25].…”
Section: Introductionmentioning
confidence: 99%
“…An zahlreichen einzelnen Beispielen konnte nachgewiesen werden, dass sich die "Protokolltreue", d. h. das personalseitige Einhalten der vereinbarten Hygienevorgaben durch Schulungsmaßnahmen, verbessern lässt, zum Beispiel im Bereich der Hän-dehygiene, der Antibiotikaprophylaxe, des Verhaltens im OP oder der OP-Technik [287,[397][398][399][400][401].…”
Section: Mitarbeiterschulungunclassified